Phytotoxic Azaphilones From the Mangrove-Derived Fungus Penicillium sclerotiorum HY5 - Wang, Wei; Wang, Mei; Wang, Xian-Bo; Li, Yi-Qiang; Ding, Ji-Lin; Lan, Ming-Xian; Gao, Xi; Zhao, Dong-Lin; Zhang, Cheng-Sheng; Wu, Guo-Xing (Frontiers in Microbiology, 2022)
Mangrove is a unique marine ecosystem growing in the intertidal zone of tropical and subtropical coast with the characteristics of hypoxia tolerance, high salinity and high humidity. In order to discover novel leading compounds with potent phytotoxicity, seven pairs of azaphilones E/Z isomers, isochromophilone H (1a/1b), sclerotiorins A and B (2a/2b and 3a/3b), ochlephilone (4a/4b), isochromophilone Ⅳ (5a/5b), isochromophilone J (6a/6b) and isochromophilone I (7a/7b), were isolated from culture broth of the mangrove-derived fungus Penicillium sclerotiorum HY5 by various chromatographic methods. Among them, 1a, 1b, 2a, 3a, 4a, 5a, 6a, and 6b were new compounds. Their chemical structures and absolute configurations were elucidated on the basis of HR-ESIMS, 1D/2D NMR spectroscopic analysis and comparisons of ECD data. Compounds 3, 4, and 7 exhibited potent phytotoxicity against the growth of radicle and plumule on Amaranthus retroflexus L., with EC50 values ranging from 234.87 to 320.84 μM, compared to the positive control glufosinate ammonium, with EC50 values of 555.11 μM for radicle, and 656.04 μM for plumule. Compounds 4 and 7 also showed inhibitory effects on the growth of velvetleaf (Abutilon theophrasti Medikus) with EC50 values ranging from 768.97 to 1201.52 μM. This study provides new leading compounds for the research and development of marine-derived bioherbicides.